Biocompatible anti-microbial coatings for urinary catheters. Issue 58 (1st June 2016) - Thompson, Vanessa C.; Adamson, Penelope J.; Dilag, Jessirie; Uswatte Uswatte Liyanage, Dhanushka Bandara; Srikantharajah, Kagithiri; Blok, Andrew; Ellis, Amanda V.; Gordon, David L.; Köper, Ingo
Abstract : Using a simple dip-coating mechanism, urinary catheters have been coated with poly(2-methacryloyloxyethyl)trimethylammonium chloride (pMTAC) using activator regenerated by electron transfer (ARGET)–atom transfer radical polymerization (ATRP). Abstract : Using a simple dip-coating mechanism, urinary catheters have been coated with poly(2-methacryloyloxyethyl)trimethylammonium chloride (pMTAC) using activator regenerated by electron transfer (ARGET)–atom transfer radical polymerization (ATRP). A polydopamine-2-bromoisobutyryl bromide (pDA-BiBBr) initiator was initially grafted to the catheter surface to initiate polymerization resulting in a pDA- g -pMTAC coating. The pDA- g -pMTAC-coated catheters showed a significant reduction in bacterial adhesion, with respect to uncoated silicone catheters, as determined by analyzing microbiological assays as well as scanning electron microscopy images. At the same time, no evidence for cytotoxicity was observed, rather, the coating promoted cell adhesion and proliferation of human cells. This makes the coating attractive for temporary as well as permanently implanted medical devices.